Pelatihan Phsycological First Aid (PFA) untuk Meningkatkan Skill Konseling Mahasiswa Bimbingan Konseling Islam - Melly Novita Sari; Baiq Aida Islahul Haq; Yessi Arba Amelia; Hernindya Septarinjani; Suryani; Fahrurrozi; Agus Sukirno; Asep Furqonuddin; Itang; Ratu Humaemah; Siti Marfu’ah; Jamaluddin; Muhamad Fadli Azim; Rezky Mehta Setiadi (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2026)
The campus environment often exposes students to academic, social, andpersonal pressures that can af ect their mental health. As a result, peer counseling becomes anessential approach to support students facing psychological dif iculties. One key skill in peer counselingis Psychological First Aid (PFA), which provides initial emotional support to individuals experiencing psychological distress. This PFA training was conducted for third-semester BKI students to enhance their ability to provide psychological support based on Islamic principles. The method used in this activity combines a literature-based socialization approach with practical exercises through seminars, discussions, and counseling simulations. The results show that while participants understood PFA theory well, some still faced dificulties in applying the techniques, especially in formulating the right questions as counselors. In conclusion, furthertraining is needed to strengthen the application of these counseling skills.